Pediatric COVID-19 and the Factors That May Mitigate Its Clinical Course - Abdel-Aziz, Mosaad; Abdel-Aziz, Nada M.; Abdel-Aziz, Dina M.; Azab, Noha (Journal of Child Science, 2020)
The clinical manifestations of novel coronavirus disease 2019 (COVID-19) vary from mild flu-like symptoms to severe fatal pneumonia. However, children with COVID-19 may be asymptomatic or may have mild clinical symptoms. The aim of this study was to investigate clinical features of pediatric COVID-19 and to search for the factors that may mitigate the disease course. We reviewed the literature to realize the clinical features, laboratory, and radiographic data that may be diagnostic for COVID-19 among children. Also, we studied the factors that may affect the clinical course of the disease. Fever, dry cough, and fatigue are the main symptoms of pediatric COVID-19, sometimes flu-like symptoms and/or gastrointestinal symptoms may be present. Although some infected children may be asymptomatic, a recent unusual hyperinflammatory reaction with overlapping features of Kawasaki's disease and toxic shock syndrome in pediatric COVID-19 has been occasionally reported. Severe acute respiratory syndrome-coronvirus-2 (SARS-CoV-2) nucleic acid testing is the corner-stone method for the diagnosis of COVID-19. Lymphocyte count and other inflammatory markers are not essentially diagnostic; however, chest computed tomography is highly specific. Factors that may mitigate the severity of pediatric COVID-19 are home confinement with limited children activity, trained immunity caused by compulsory vaccination, the response of the angiotensin-converting enzyme 2 receptors in children is not the same as in adults, and that children are less likely to have comorbidities. As infected children may be asymptomatic or may have only mild respiratory and/or gastrointestinal symptoms that might be missed, all children for families who have a member diagnosed with COVID-19 should be investigated.
Keywords: coronavirus; COVID-19; SARS-CoV-2 infection; pediatric infection; trained immunity